Duties and Responsibilities of Educational Management - Susanto, Edy; Kumar, K Sathish (PPSDP International Journal of Education, 2022)
This study aims to describe the duties and responsibilities of education management. This study uses a literature study. The object of this research is the duties and responsibilities of education management. The results of the study concluded that if the duties and responsibilities were carried out properly, the school would be good too, especially in the 4.0 era. This article provides insight to be good principal.